Trucking wellness : an industry's response to managing HIV/AIDS - Townsend, Stephanie (SAGE knowledge. Cases., 2016)
In 2012, South Africa was still one of the countries with the highest prevalence of HIV/AIDS in the world. Statistics SA estimated that in 2011, 10.6% of the total population and 16.6% of the adult population (people between 15 and 49 years of age) were HIV positive. This text examines the response of the South African truck haulage industry to the challenges posed by HIV/AIDS.